Kontaminasi Logam Berat Timbal (Pb) Dan Kadmium (Cd) Pada Sedimen Estuari Baturusa, Kota Pangkalpinang - Maulinda Huzairiah; Mohammad Agung Nugraha; Aditya Pamungkas (Journal of Tropical Marine Science, 2022)
The Baturusa River watershed has mining, fishing, industrial, and ship berthing activities. Activities carried out either directly or indirectly in the river can trigger the potential for pollution. Heavy metals are hazardous pollutants which, if present in large quantities, affect various aspects of the waters, both biologically and ecologically. The aim of this study was to determine the concentration of heavy metals Pb and Cd as well as the level of metal contamination of Pb and Cd (CF/ contamination factor, I-Geo/ Geoaccumulation Index) EF/ Enrichment factor) in the sediments of the Baturusa River Estuary, Pangkalpinang City. Heavy metals were analyzed by the AAS method. The concentration of Pb and Cd in the Baturusa River Estuary sediment has not exceeded the limit range based on the quality standards specified in the ISQG and PEL CCME 2002. The value of the heavy metal contamination factor (CF) of Pb found in the Baturusa Estuary sediment ranged from 0.00029–0.00042 ( CF